MODEL PEMBERDAYAAN KELOMPOK PENCUCIAN SARANG BURUNG WALET MELALUI TEKNOLOGI PRODUKSI DAN PEMASARAN ONLINE - Hadi, Dwi Prastiyo; Sutrisno, Sutrisno; Muflihati, Iffah (Jurnal Abdi Insani, 2024)
Kalikayen village has 11 swallow nest washing groups, namely 1) Ibu Sulasih with 25 employees, 2) Ibu Suniati with 20 employees, 3) Ibu Nita with 15 employees, 4) Ibu Wikomsiatun with 20 employees, 5) Ibu Mutrikah with 20 employees, 6) Mrs. Sriyatun with 20 employees, 7) Mrs. Ramija with 13 employees, 8) Mrs. Maerokah with 19 employees, 9) Mrs. Rosidah with 15 employees, 10) Mrs. Mais with 9 employees, 11) Mrs. Rubiyanti with 17 employees. The 11 groups have problems, namely 1) they are still individuals and on their own, there is no good production management and financial management, they are confused about accessing capital to banking institutions, and they have not utilized online marketing. The aim of this service is to increase the community income of the swallow's nest washing group in Kalikayen village, Semarang Regency by increasing product quality and quantity in swallow's nest washing, increasing working capital obtained from government access or competent banking, and increasing business networks with the community. partners and the existence of an online shop. The method of this activity is empowerment, namely there are stages of activities in implementing PKM. These stages are as follows; (1) Socialization of PKM activity programs; (2) formation of partner organizational structures; (3) development of production management and financial administration; (4) Workshop on methods for accessing capital from Government and Private Agencies; (5) Swallow's Nest Processing Workshop; (6) Online marketing training; and (7) Evaluating the results of the activities of the PKM swallow nest washing group in Kalikayen village, Semarang Regency. The results of service activities are (1) the community understands and supports the PKM activity program; (2) the formation of an association for swallow nest washing groups; (3) there is an increase in swallow nest production and bookkeeping administration (4) there is cooperation with banks in capital both individually and in groups (5) there is an increase in the quality of swallow nests in accordance with export standards, namely 90%, (6) there is an online shop in market place tokopedia, bukalapak, sopee. The conclusion is that by empowering the swallow nest washing group, the income of the swallow nest washing group in Kalikayen village, Semarang Regency increased by 40%, followed by an increase in product quality and quantity in swallow nest washing, increased working capital obtained from government access. or competent banking, and increasing business networks with partners and the existence of online stores